2015
DOI: 10.3791/52325
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Repeated Exposure of Organotypic 3D Bronchial and Nasal Tissue Culture Models to Whole Cigarette Smoke

Abstract: Cigarette smoke (CS) has a major impact on lung biology and may result in the development of lung diseases such as chronic obstructive pulmonary disease or lung cancer. To understand the underlying mechanisms of disease development, it would be important to examine the impact of CS exposure directly on lung tissues. However, this approach is difficult to implement in epidemiological studies because lung tissue sampling is complex and invasive. Alternatively, tissue culture models can facilitate the assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…The observed VEGF and IL-8 response at 24 hours postexposure and MCP-1 reduction at 48 hours were in agreement with previous work conducted using the same cell type and a similar short repeated exposure smoking regimen of a 3R4F reference cigarette. 28,34 Furthermore, studies using sample sources such as primary and immortal human bronchial epithelial cells, peripheral blood mononuclear cells, and sputum have shown that cigarette smoke exposure stimulates the expression of MMP-9, IL-8, VEGF, 35 IL-4, 36 and IL-6 37 in the pathogenesis of COPD, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The observed VEGF and IL-8 response at 24 hours postexposure and MCP-1 reduction at 48 hours were in agreement with previous work conducted using the same cell type and a similar short repeated exposure smoking regimen of a 3R4F reference cigarette. 28,34 Furthermore, studies using sample sources such as primary and immortal human bronchial epithelial cells, peripheral blood mononuclear cells, and sputum have shown that cigarette smoke exposure stimulates the expression of MMP-9, IL-8, VEGF, 35 IL-4, 36 and IL-6 37 in the pathogenesis of COPD, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These two MMPs and two cytokines are well-documented responders to cigarette smoke in the airways. 28 A significant increase in MMP-1 expression was observed in three donors D1, D3, and D6 in response to whole smoke exposure (Fig. 4).…”
Section: Donor Selectionmentioning
confidence: 81%
See 3 more Smart Citations